Role of the overriding plate in the subduction process - Chen, Zhihao (Monash University. Faculty of Science. School of Earth, Atmosphere and Environment, 2015)
Subduction zones are thought to be the main driver of plate tectonics and mantle convection. Since the development of the theory of plate tectonics, subduction zones have been investigated and discussed, but in many ways they are still an enigma. Geodynamic modelling (analogue or numerical) can be an effective tool to gain insight into the temporal evolution of subduction zones as it provides quantitative and conceptual insights into the interactions between the plates, the slab and the mantle. Moreover, modelling results can then be compared to their natural prototypes providing crucial insight into regional processes. In my PhD project I use four-dimensional laboratory-based (analogue) geodynamic models to investigate the kinematics and dynamics of subduction, with a particular emphasis on the deformation in the overriding plate. I then compare and constrain my results with natural observations from subduction zones. My thesis has been divided into two parts. The first part focuses on the patterns of overriding plate deformation during progressive subduction when some parameters of the overriding plate are varied. In the first work (Chapter 4), the strength of the overriding plate (i.e., viscosity ratio between the overriding plate and the sub-lithospheric upper mantle, and the overriding plate thickness) is varied to quantify the energy dissipation of overriding plate deformation. The results show that only a small portion of the slab negative buoyancy force and its potential energy are used to deform the overriding plate, and the force required to deform the overriding plate is comparable in magnitude with the ridge push force. Furthermore, the results also show that the bending dissipation at the subduction zone hinge remains relatively low (during steady state subduction), irrespectively of including/excluding an overriding plate in the models. In the second work (Chapter 5), far-field boundary conditions of the overriding plate and subducting plate are varied. The results indicate that such a variation has an influence on the slab geometry and subduction kinematics. The models imply that in natural (narrow) subduction zones, assuming a homogeneous overriding plate, the formation of a backarc basin (e.g., Tyrrhenian Sea, Aegean Sea, Scotia Sea) is generally expected to occur at a comparable location with respect to the trench, irrespective of the boundary condition. In addition, my models indicate that the style of forearc deformation (shortening or extension) is affected by the mobility of the overriding plate through controlling the force normal to the subduction zone interface (trench suction). Finally, the results of the model with both plates fixed at their trailing edges are applied to the Calabria subduction zone. This model explains the latest Middle Miocene to present backarc and forearc extension at the Calabria subduction zone as a direct consequence of subduction of the narrow Calabrian slab and the immobility of both the subducting African plate and overriding Eurasian plate. The second part of this thesis focuses on the role of subduction-induced mantle flow in driving deformation of the overriding plate, including (horizontal) trench-normal backarc deformation (Chapter 6) and topography of the overriding plate (Chapter 7). In Chapter 6, a stereoscopic Particle Image Velocimetry (sPIV) technique was used to map simultaneously the horizontal overriding plate deformation and the 3D subduction-induced mantle flow underneath and around the overriding plate. The results show that the strain field of the overriding plate is characterized by localization of an area of maximum extension within its interior (at 300-500 km from the trench). The position of this maximum extension corresponds to that of the maximum trench-normal horizontal velocity gradient measured in the mantle at a scaled depth of 15-25 km below the base of the overriding plate. The results robustly support the hypothesis that in narrow subduction zones backarc extension in the overriding plate is mainly a consequence of the trench-normal horizontal gradients of basal drag force at the base of overriding plate. Such gradients result from a differential in the mantle flow velocity field induced by slab rollback. In Chapter 7, I also used the sPIV technique to investigate the vertical displacement of the overriding plate in a self-consistent subduction model with free boundary conditions. It is suggested that the trench suction force normal to the subduction zone interface, in combination with the shear force at the interface, has an overall influence on the topography of the overriding plate, through bending the overriding plate downward at the trench. Furthermore, the overriding plate is characterized by a transient topographic subsidence located in the forearc, at ~2-5 cm (scaling to 100-250 km) from the trench, with a magnitude of 0.65-1.35 mm (scaling to 3.25-6.75 km). These transient features are most pronounced during the early, transient, free slab sinking phase and predominantly results from the variation of the vertical component of the trench suction along the subduction zone interface, which is induced by the gradual slab steepening during this early phase. The downward mantle flow in the nose of the mantle wedge plays a minor role in the forearc subsidence.